Analisis Kinerja Keuangan BMT Al-Ittihat Pekanbaru - Masnur Masnur; Wiwik Anggraini; Rasya Kinaya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
BMT financial performance is a description of the financial condition of a BMT which is analyzed using financial analysis tools, so that it can be known about the good and bad financial condition of a company which reflects work performance in a certain period. Good financial performance can be assessed from the results of analysis that obtain performance in accordance with established standards. The resulting problem formulation is how the financial performance of BMT AL-Ittihad Pekanbaru increases its revenue. The analytical method used is a quantitative descriptive method, percentage, namely by explaining existing data which is then processed and produces results in the form of a presentation. The ratio analysis used in measuring finances is the carren ratio, asset turnover, net profit margin and rate of return, investment (ROI). The overall analysis carried out produces stable ratio figures. Financial performance that occurs in BMT Al-Ittihad Pekanbaru's income quite stable in terms of cost efficiency because if operational expenditure (costs) increase then income increases and conversely if operational expenditure (costs) decrease then income decreases. The research results show that the remaining business results are obtained from income minus operational expenses (costs). The stability of the remaining business results of BMT Al-Ittihad Pekanbaru is proven to increase every year, meaning that BMT Al-Ittihad Pekanbaru's income every year is always greater than expenses.The remaining business results for the last five years can also be maintained in stability, such as in 2018 the net profit obtained was relatively large compared to 2019 but accompanied by small costs so that the profit generated was also relatively stable In 2019, the remaining operating results decreased from 2018 by 0.44%, but coupled with an increase in costs, the profits generated were also relatively stable. In 2020, the remaining operating results increased by 0.43%, but coupled with the increase in costs, the profits generated were also relatively stable. In 2021, net profit decreased by 0.23%, coupled with an increase in costs, the resulting profit was also relatively stable. In 2021 it will decrease again and increase to 0.42% Keywords: Carren Ratio, Asset Turn Over, Net Profir Margin dan Rate of Return Invesment (ROI).